Ambidextrous Innovation in the Platformization Era: The Role of ESG Capability, Marketing Innovation, and IT Capability in Building Local Media Resilience - Hidayatullah, Rahmat; Al Bushairi, Siti Aliyati; Huda, Nuril (Jurnal Manajemen, 2026)
Platformization has disrupted the revenue architecture, audience relationships, and competitive position of local media firms, making corporate resilience a central strategic concern. However, prior studies have largely examined ESG capability, marketing innovation, and IT capability in isolation, providing limited explanation of how these capabilities jointly build resilience in platform-dependent media markets. This conceptual study develops an integrative framework through a structured narrative literature review and theory synthesis of peer-reviewed studies published between 2010 and 2025. The review focuses on six constructs: ESG capability, marketing innovation, IT capability, ambidextrous innovation, environmental turbulence, and corporate resilience. The synthesis indicates that ESG capability strengthens legitimacy, stakeholder trust, and governance quality; marketing innovation renews value propositions and revenue logic; and IT capability improves sensing, coordination, and digital reconfiguration. Ambidextrous innovation is positioned as a partial mediating mechanism through which these capabilities are translated into corporate resilience, while environmental turbulence is proposed as a boundary condition that intensifies the strategic value of ambidexterity under rapid technological, market, and regulatory change. By integrating sustainability and dynamic capability perspectives, this study offers a platformization-aware model of local media resilience, formulates testable propositions, and provides a foundation for future empirical research.